Melatonin Receptor Agonists for the Prevention of Delirium: An Updated Systematic Review and Meta-Analysis of Randomized Controlled Trials - Maneeton, Benchalak; Kongsaengdao, Subsai; Maneeton, Narong; Likhitsathian, Surinporn; Woottiluk, Pakapan; Kawilapat, Suttipong; Srisurapanont, Manit (Current Neuropharmacology, 2022)
Background: Although a previous review illustrated the efficacy of melatonin receptor agonists (MRAs) in preventing delirium, some recent randomized controlled trials (RCTs) did not confirm these effects. Objectives: This study systematically reviewed the efficacy, acceptability, and tolerability of MRAs for delirium prevention. Materials and Methods: We searched electronic databases, including Scopus, PubMed, CINAHL, and Controlled Trials Register, from their inception to February 20, 2022. The primary efficacy outcome was delirium incidence rate after MRA administration; relative risks (RRs), overall discontinuation, and discontinuation due to adverse events are also presented. Results: The overall pooled incidence rates of delirium in MRA-treated and placebo-treated groups were significantly different with RR (95% CI)=0.66(0.52, 0.84, ), I2=59%. Similarly, the incidence rate was significantly lower in the melatonin-treated group than in the placebo-treated group [RR (95% CI) =0.65 (0.49, 0.88), I2=65%]. Unfortunately, incidence rates were not significantly different between ramelteon-treated and placebo-treated groups [RR (95% CI) =0.67 (0.42, 1.08), I2=50%]. The pooled incidence rate of delirium in either melatonin or ramelteon-treated groups was not significantly different from the placebo-treated group in elderly patients. The pooled incidence rate of delirium was significantly lower in the melatonin-treated group than in the benzodiazepinetreated group. Conclusion: Based on this review, melatonin could prevent delirium with a small effect size. However, ramelteon did not show efficacy in preventing delirium. Additionally, neither melatonin nor ramelteon individually showed effectiveness in preventing delirium in elderly patients. Therefore, using MRAs to prevent delirium in clinical practice should be cautious. However, future welldefined and large sample size studies could verify these findings.
Keywords: incidence